A prospective investigation into the reasons why insured United States patients drop out of in vitro fertilization treatment - Domar, Alice D.; Smith, Kristin; Conboy, Lisa; Iannone, Marie; Alper, Michael (Fertility and sterility, 2010)
To determine the primary reason why insured patients drop out of IVF treatment in the United States and to identify methods to decrease such behavior. Prospective patient survey. Private infertility clinic. Women under the age of 40 years, who had insurance coverage for at least three IVF cycles, who did not conceive and who did not return to the clinic for a third treatment cycle. One hundred thirty-two eligible patients received a study packet of questionnaires in the mail. Subject responses to questionnaire. Forty-seven subjects returned the questionnaire. The most common reason for terminating treatment was stress (39%). Subjects reported that the two main causes of stress were the toll that infertility took on the couples' relationship and being too anxious or depressed to continue. The top-rated suggestions for patient support were written information on how to deal with psychological stress and easy and immediate access to a psychologist or social worker. Patients undergoing IVF in the United States report similar reasons for terminating treatment as patients in Europe and Australia. However, this is the first study to gather patient suggestions for treating the problem.